A new cecidogenous species of Eugnosta Hübner (Lepidoptera: Tortricidae) associated with Baccharis salicifolia (Asteraceae) in the northern Chilean Atacama Desert: Life-history description and phylogenetic inferences - Vargas, Héctor A.; Pollo, Pietro; Basilio, Daniel S.; Gonçalves, Gislene L.; Moreira, Gilson R. P. (Zootaxa, 2015)
Eugnosta Hübner, 1825 (Lepidoptera, Tortricidae, Tortricinae, Cochylini, Cochylina) is reported for the first time in Chile. Male and female adults, the pupa, the last-instar larva, and galls of Eugnosta azapaensis Vargas & Moreira, sp. n., are described and illustrated from the Azapa Valley in the northern Atacama Desert. The larvae induce fusiform galls on shoots of the shrub Baccharis salicifolia (Ruiz & Pav.) Pers. (Asteraceae). An assessment of phylogenetic relationships of E. azapaensis with two congeneric species based on mitochondrial DNA is provided.